2006
DOI: 10.1128/aac.00477-06
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bactericidal Activity of Extended-Release Ciprofloxacin (1,000 Milligrams) versus Levofloxacin (500 Milligrams) in Healthy Volunteers Receiving a Single Oral Dose

Abstract: Twelve volunteers received a single oral dose of 1,000 mg extended-release (XR) ciprofloxacin versus 500 mg levofloxacin to assess urinary bactericidal titers (UBTs) against common uropathogens. Areas under UBT-time curves were significantly larger for Proteus mirabilis with XR ciprofloxacin and for staphylococci with levofloxacin.Complicated urinary tract infections (UTIs) are caused by gram-negative and -positive uropathogens (25). Fluoroquinolones are among the drugs of choice for empirical antibiotic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…UBTs have been shown to serve as valuable pharmacokinetic/pharmacodynamic parameters predicting urinary antibacterial efficacy in the assessment of fluoroquinolones (28,(31)(32)(33). In a study with patients with complicated UTIs, the UBT and AUBT 24 values for levofloxacin were highly correlated with clinical and/or microbiological success or failure (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UBTs have been shown to serve as valuable pharmacokinetic/pharmacodynamic parameters predicting urinary antibacterial efficacy in the assessment of fluoroquinolones (28,(31)(32)(33). In a study with patients with complicated UTIs, the UBT and AUBT 24 values for levofloxacin were highly correlated with clinical and/or microbiological success or failure (34).…”
Section: Discussionmentioning
confidence: 99%
“…In order to integrate pharmacokinetic and pharmacodynamic parameters, the urinary inhibitory titers (UITs), urinary bactericidal titers (UBTs), and urinary bactericidal kinetics (UBK) for common uropathogens were determined after oral administration of recommended therapeutic doses of 250 mg NTX and 200 mg TMP (26)(27)(28). NTX is excreted in the urine in unconjugated as well as conjugated (e.g., glucuronide and sulfate) forms (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Higher urinary concentrations of magnesium, which are commonly in the range of 8–10 m M , in combination with a low pH value account in large part for this reduction in activity [7,22,23]. For the treatment of UTI, the bactericidal activity of an antibacterial agent measured in urine is therefore considered to be a helpful pharmacodynamic parameter [16,17,30] that has also been shown to be accurate and reproducible [31]. The urine AUC/minimal bactericidal concentration (MBC) ratio relates directly to the AUBT because the reciprocal UBT indicate the urinary concentrations divided by the MBC as determined in urine.…”
Section: Discussionmentioning
confidence: 99%
“…[8,12,15,19,14]. [18] showed that ciprofloxacin XR possessed larger AUCs than levofloxacin. Patients' compliance improvement using ciprofloxacin XR and thus decrease the risk of treatment failure and the spread of antibiotic resistance are also reported [17].…”
Section: Introductionmentioning
confidence: 99%